Pulmonary and Bronchiolar Involvement in Sjogren's Syndrome - Chung, Augustine; Wilgus, May Lin; Fishbein, Gregory; Lynch, Joseph P., III (Seminars in Respiratory and Critical Care Medicine, 2019)
Sjogren's syndrome (SS) is a chronic autoimmune disease characterized by mononuclear cells (principally lymphocytes) infiltrating exocrine glands (e.g., salivary and lacrimal glands), leading to destruction of exocrine epithelial cells and dryness of mucosal surfaces. Cardinal symptoms are dry eyes (xerophthalmia) and dry mouth (xerostomia). Extraglandular sites are affected in 30 to 40% of cases of SS (particularly neurological, kidneys, skin, and lungs). B cell hyperactivity, autoantibody production, and hypergammaglobulinemia are cardinal features of SS. Primary SS is not associated with other autoimmune diseases. However, SS can complicate diverse autoimmune disorders (particularly systemic lupus erythematosus, rheumatoid arthritis, and scleroderma); this form is termed “secondary SS.” Pulmonary involvement is usually not a dominant feature of SS, but may be severe in some cases. In this review, we discuss specific tracheal, bronchiolar, and pulmonary complications of SS including xerotrachea, bronchiolitis, bronchiectasis, interstitial lung disease, nonspecific interstitial pneumonia, usual interstitial pneumonia, lymphoid interstitial pneumonia, organizing pneumonia, acute fibrinous and organizing pneumonia, pulmonary cysts, pleural effusions, pulmonary amyloidosis, and bronchus- or lung-associated lymphomas.
Keywords: connective tissue disease; Sjogren's syndrome; lymphocytic interstitial pneumonia; follicular bronchiolitis; interstitial lung disease; cystic lung disease